Blood contamination in neonates: clinicians’ dilemma - R Iyer, Chandrakala; PJ, Harsha; G, Naveen; Katwe, Nagendra (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal sepsis is an important cause of mortality and morbidity among neonates. Many laboratory tests aid to diagnose sepsis but isolation of bacteria in the blood is the gold standard for diagnosis of sepsis. Growth of contaminants in the blood nullifies the utility of blood culture. Coagulase Negative Staphylococcus aureus (CoNS) is a common blood contaminant, but it can be a pathogen among neonates admitted to intensive care unit. Difficulty in differentiating true infection of CoNS from blood contamination can results in inappropriate treatment of contaminants with antibiotics like vancomycin. There are advanced microbiological tests to distinguish true growth of CoNS from contaminants but they are not easily available and not cost effective in developing countries. There were numerous blood culture reports of CoNS and other contaminants from our neonatal intensive care unit of a rural based medical college hospital. Aim and objectives of the study were to differentiate true infection with positive blood cultures by correlation of clinical features, risk factors and clinical setting for CoNS sepsis. Methods: Retrospective case record analysis of 50 positive blood cultures for clinical significance of blood contaminants including CoNS. Results: Clinical correlation showed that 39 culture reports were false positives. Five positive blood cultures had pathogenic bacteria and six positive culture reports with blood contaminates and CoNS were true infection needed treatment with escalation of antibiotics. Conclusions: The source of blood contamination was from hospital environment probably due to lack of proper hand hygiene and blood sampling method. Implementation of quality control strategies on hand wash and blood collection method can reduce blood contamination.